Reclaiming Childbirth: A DES Mother and Daughter’s Tale - Pershing, Linda (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
This is a personal narrative about the author’s struggles with exposure to des (diethylstilbestrol)and subsequent decision to use natural childbirth methods when herdaughter was born. Her story illustrates the power of women’s decision-making indefining their own birthing experiences.